Heart rate variability and metabolic rate in healthy young adults with low birth weight - Weitz, Gunther (e-Century Publishing Corporation, 2013)
Objective: Low birth weight (LBW) is associated with obesity and a higher cardiovascular risk in adult life. Since autonomic dysfunction could be a pathophysiological factor for this association, we assessed the impact of LBW on cardiac autonomic activity and metabolic rate in young adulthood. We hypothesized that the autonomic tone could be coupled with the metabolic rate in subjects with LBW. Methods: Heart rate variability (HRV) from 24-hour Holter-electrocardiograms was measured in 15 healthy adults aged 20 to 30 years with LBW (<2500g at term) and 15 paired subjects with normal birth weight (NBW). The pairs were closely matched by gender, age, and body mass index. Resting energy expenditure was measured by indirect calorimetry and body composition by bioimpedance. Results: Global HRV parameters were significantly higher in the LBW group and a marked difference was observed in the long wave fluctuations of the frequency domain (very low frequency). These fluctuations were positively correlated with the resting energy expenditure per body weight in the LBW and negatively in the NBW group. Only in the LBW group HRV was closely related to body fat. Interpretation: This case-control study indicates that autonomous nervous function is not generally deteriorated in young adults with LBW and has a significant association with metabolic rate. Thus, it may be a determinant of the body weight regulation in this group. The higher cardiovascular risk in ageing individuals with LBW would therefore rather be a consequence of weight gain than of a primary autonomous nervous dysfunction.